Manajemen Pengembangan Kompetensi Guru sebagai Determinan Kinerja Guru - Januar Barkah; Achmad Sarwandianto (Departement of Mathematics Education, 2023)
Teacher performance is a very determining factor for the quality of education, which will have an impact on the quality of graduates after finishing school. Competence in the last decade has become an important issue and made every teacher empowerment in improving the quality of education in Indonesia at this time, so researchers are interested in discussing the management of teacher competency development as an effort to take part in providing education, especially teacher competency development management. The purpose of this study is to determine the management of teacher competency development as a determinant of teacher performance. The type of research used is quantitative descriptive research. There is an influence of teacher competency development management on teacher performance. It is based on a value of R2 (R Square) of 0.68. This shows that 68% of Teacher Competency Development Management has a positive effect on teacher performance.